RESEARCH AND FORECASTING OF FERTILITY IN THE TASHKENT REGION OF THE REPUBLIC OF UZBEKISTAN (Web of Technology: Multidimensional Research Journal, 2025)
This study is aimed at analyzing and forecasting the birth rate in the Tashkent region of the Republic of Uzbekistan. The work examines the key factors influencing fertility, including the economic, social and demographic conditions of the region. Particular attention is paid to the collection and analysis of statistical data provided by the State Committee of Statistics of the Republic of Uzbekistan, as well as demographic modeling methods to assess future trends. The purpose of the study is to assess current trends in fertility, identify the main determinants affecting its level, and based on the data obtained, make forecasts for the coming years. The work also offers recommendations for public policy to increase fertility rates, improve conditions for families, and support reproductive health. The results of the study may be useful for developing effective social and economic programs aimed at stimulating the birth rate in the Tashkent region, as well as for making decisions in the field of social policy and demographic development of the region.